Information, Intermediaries, and International Migration - Samuel Bazzi; Lisa A. Cameron; Simone G. Schaner; Firman Witoelar (Institute of Labor Economics (IZA), 2021)
Job seekers often face substantial information frictions related to potential job quality. This is especially true in international labor markets, where intermediaries match prospective migrants with employers abroad. We conducted a randomized trial in Indonesia to explore how information about intermediary quality shapes migration choices and outcomes. Information reduces the migration rate, lowering use of low-quality intermediaries. However, workers who migrate receive better pre-departure preparation and have higher-quality job experiences abroad, despite no change in occupation or destination. Information does not change intentions to migrate or beliefs about the return to migration or intermediary quality. Nor does selection explain the improved outcomes for workers who choose to migrate with the information. Together, our findings are consistent with an increase in the option value of search: with better ability to differentiate offer quality, workers become choosier and ultimately have better migration experiences. This offers a new perspective on the importance of information and matching frictions in global labor markets.
Keywords: F22; O15; D83; L15; 330; international migration; information; middlemen; quality disclosure; search